Penanggulangan Orang Asing Yang Menjadi Korban Perdagangan Orang dan Penyeludupan Manusia di Bidang Keimigrasian - Zeleta Feba Haprifanyuna; Mohammad Iqbal; Raditya Pandya Kusuma (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Indonesia is a country that attracts the attention of foreigners to visit Indonesia. The number of foreign enthusiasts to visit the territory of Indonesia makes immigration a gateway for a country that is very picky in allowing foreigners to enter Indonesia. procedures that are deemed too difficult, individuals appear who can make it easier for foreigners to enter Indonesian territory. because of this, many people take advantage of it to gain profits by committing crimes in the form of human trafficking and people smuggling. This study describes the handling of foreigners who are victims of human trafficking and people smuggling in accordance with existing laws and regulations. In addition, the implementation of statutory regulations in terms of handling foreigners who become victims of trafficking in persons and people smuggling has been carried out by the Immigration Office in the form of placing foreigners in the Immigration Detention Center or other designated places without being subject to Immigration Administrative Actions and also different handling with detainees for other cases, as well as managing files and data from victims of trafficking in persons and people smuggling so that they can be immediately repatriated to their countries of origin. In repatriating victims to their countries of origin, immigration cooperates with the ministry of foreign affairs to coordinate with state representatives in Indonesia.